PENGELOLAAN SEKOLAH BERBASIS MUTU STUDI SITUS DI SMA ASSALAAM SUKOHARJO - Praptini, Ninik (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2014)
The purpose of the study are: 1) To get a description about the condition ofeducation quality in general in SMA Assalaam Sukoharjo, in order to describethe real fact of the education quality in SMA Assalaam Sukoharjo; 2) to revealthe condition of students achievement in order to describe the success level of the educationquality in SMA Assalaam Sukoharjo; 3) to reveal the quality management in SMA AssalaamSukoharjo that consists of classroom management, student recruitment management andlearning activity management. The research is beneficial as the consideration for theheadmaster in conducting evalution in the teaching and learning activity and as informationabout the quality management in SMA Assalaam Sukoharjo.